RED TIDE DETECTION USING Seawifs STANDARD CHOLOROPHYLL-a ALGORITHM IN SOUTHEAST KOREAN WATERS - Gathot Winarso (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2012)
Cochlodinium  polykrikoides  red  tides  have  occurred  in  summer  every  year  at coastal  waters  of  the  South  Korea.  Chlorophyll-a  concentration  data  estimated  from  ocean color satellite SeaWiFS (Sea-viewing Wide Field-of-view  Sensor)  were  used to detect the red tide in this study. The high value of chlorophyll-a concentration used  to detect red tide was analyzed  and   compared  with  red  tide  map  produced  by  National  Fisheries  Research  and Development Institute of Korea (NFRDI). Based on SeaWiFS data and NFRDI red tide map, it was  found  that  high  chlorophyll-a concentration  of  ≥  5  mg/m3in  SeaWiFS  images corresponded to the red-tide occurrence with some limitations.